Comparison of Covid-19 knowledge, attitudes, and preventive behavior between nursing students and other major students - Na eun, Kim; Nam hee, Kim; Ha yeon, Kim; Sung min, Lim; Min seo, Jin; Eun jeong, Jin (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
Introduction : Coronavirus infection-19 is now emerging as a worldwide infection. Unlike before, covid-19 has a fast spread of infection, and the incidence rate is increasing at an uncontrollable rate as no proven treatment has been developed. In particular, according to statistics by age of confirmed patients in Korea, the age of people in their 20s has the highest incidence rate, which is believed to be due to their higher activity compared to other ages. Purpose : university students should accurately recognize and implement infection control and prevention guidelines to maintain their health and prevent the spread of infection. In particular, nursing college students need to be careful not only because they are future medical personnel but also because they can be a source of infection for patients if they participate in clinical practice. Methodology : In this study, we decided to compare the relationship between covid-19 knowledge, attitudes, and implementation of infection prevention activities, and identify and compare the differences between nursing and other major engineering students. Naver form questionnaires were distributed to 80 students attending a four-year university and a technical university in Daegu. The collected data were used for technical statistics, T-test and correlation analysis using the SPSS 18 program. Findings : Significant relationships were drawn to Corona 19 related knowledge and attitudes, showing a positive attitude with higher knowledge levels, which also showed significant relationships in the implementation of infection prevention behaviors. Compared to other college students, nursing college students showed significantly higher levels of knowledge related to covid-19, and their attitude and implementation of infection prevention activities also showed higher scores on average, but did not show significant results. Originality : Based on the results of the study, even nursing college students, including some other college students, could identify the level of knowledge, attitudes, and implementation of infection prevention activities related to covid-19, and can be used to develop effective education guidelines.